2023
DOI: 10.1021/acs.langmuir.3c00568
|View full text |Cite
|
Sign up to set email alerts
|

Can the Sublimation Enthalpy Be Obtained Using Atomic Force Microscopy with Heating? A PETN Nanofilm Case

Abstract: Vaporization is an important aspect of the performance and detection of energetic materials. While the traditional techniques concentrate on bulk property changes during sublimation, atomic force microscopy (AFM) offers the possibility to track particle volume changes under heating. Ideally, this will enable the investigation of chemicals that are challenging to study using conventional vaporization analysis methods, i.e., those having low thermal stability and/or low volatility. However, prior studies have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…It is important to note that this study cannot quantify the relative contributions of what we assume to be faster surface diffusion versus slower sublimation processes that can occur over longer periods of time. This is a possible explanation for why the activation barrier found for this study is larger than the value found by Gee et al Furthermore, a recent study on sublimation in PETN nanofilms reported activation barriers of roughly 126 kJ mol –1 , in reasonable agreement with our estimate . At the lower temperatures of 50 and 60 °C, we assume that surface diffusion dominates over sublimation processes, even at the longer aging times.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is important to note that this study cannot quantify the relative contributions of what we assume to be faster surface diffusion versus slower sublimation processes that can occur over longer periods of time. This is a possible explanation for why the activation barrier found for this study is larger than the value found by Gee et al Furthermore, a recent study on sublimation in PETN nanofilms reported activation barriers of roughly 126 kJ mol –1 , in reasonable agreement with our estimate . At the lower temperatures of 50 and 60 °C, we assume that surface diffusion dominates over sublimation processes, even at the longer aging times.…”
Section: Discussionsupporting
confidence: 89%
“…This is a possible explanation for why the activation barrier found for this study is larger than the value found by Gee et al Furthermore, a recent study on sublimation in PETN nanofilms reported activation barriers of roughly 126 kJ mol –1 , in reasonable agreement with our estimate. 28 At the lower temperatures of 50 and 60 °C, we assume that surface diffusion dominates over sublimation processes, even at the longer aging times. At the higher temperature of 75 °C, we assume that both surface diffusion and sublimation contribute at the early time points, which is inherently included in the Arrhenius analysis for coarsening and results in a larger E a value.…”
Section: Discussionmentioning
confidence: 99%